At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
Step-by-step explanation:
f
(
x
)
=
x
3
−
6
x
2
+
11
x
−
6
Reemplace
f
(
x
)
con
y
.
y
=
x
3
−
6
x
2
+
11
x
−
6
Para hallar las raíces de la ecuación, remplazar
y
por
0
y resolver.
0
=
x
3
−
6
x
2
+
11
x
−
6
Reescriba la ecuación como
x
3
−
6
x
2
+
11
x
−
6
=
0
.
x
3
−
6
x
2
+
11
x
−
6
=
0
Factorizar el lado izquierdo de la ecuación.
Toca para ver más pasos...
(
x
−
3
)
(
x
−
2
)
(
x
−
1
)
=
0
Establezca la
x
−
3
igual a
0
y resuelva para
x
.
Toca para ver más pasos...
x
=
3
Establezca la
x
−
2
igual a
0
y resuelva para
x
.
Toca para ver más pasos...
x
=
2Reemplace
f
(
x
)
con
y
.
y
=
x
3
−
6
x
2
+
11
x
−
6
Para hallar las raíces de la ecuación, remplazar
y
por
0
y resolver.
0
=
x
3
−
6
x
2
+
11
x
−
6
Reescriba la ecuación como
x
3
−
6
x
2
+
11
x
−
6
=
0
.
x
3
−
6
x
2
+
11
x
−
6
=
0
Factorizar el lado izquierdo de la ecuación.
Toca para ver más pasos...
(
x
−
3
)
(
x
−
2
)
(
x
−
1
)
=
0
Establezca la
x
−
3
igual a
0
y resuelva para
x
.
Toca para ver más pasos...
x
=
3
Establezca la
x
−
2
igual a
0
y resuelva para
x
.
Toca para ver más pasos...
x
=
2
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.